PENDEKATAN PENYULUHAN PARTISIPATIF DALAM PEMBERDAYAAN MASYARAKAT BERBASIS BUDAYA LOKAL DI DESA KAMPUNG BARU KECAMATAN KOTA AGUNG - Hidayat, Mansur (KOMUNIKA, 2018)
In the perspective of social change based on the empowerment paradigm, development communication activities as a process of change are also carried out in a participatory manner. The process of participation and empowerment can be studied through awareness theory. a process of awareness to them about the circumstances of the environment, needs, desires, and abilities. The awareness process must be done through a dialogue process. While the process of dialogue is a continuous two-way communication process so as to find an understanding and understanding that form an awareness.  This awareness will happen to the dialogue parties. Such parties can be individuals in the community as well as individuals in government institutions. Communication process is often referred to as a model of convergence communication. Implementation of participatory extension approach is the most appropriate approach to be used in the process of community empowerment, because besides it will naturally give rise to a collective awareness of the problem and its potential, it will also place the community as subject and responsible actors of change.